Some Historical Briefs and Outlooks of the Chemical and Biological Acid Leaching of Uranium Ores - Bhatti, Tariq M.; Tuovinen, O.H. (The Nucleus, 2023)
The purpose of this paper is to briefly review early developments in the chemical and biological acid leaching of uranium ores in Portugal, Canada, Sweden, Finland, Estonia, and Pakistan. Uranium exists in tetravalent (U(IV)) and hexavalent (U(VI)) oxidation states in igneous, metamorphic, and sedimentary mineral deposits. Acidic ferric sulfate is a chemical oxidant of tetravalent uranium and is regenerated from ferrous iron in the leachate and produced also from pyrite (FeS2, cubic), marcasite (FeS2, orthorhombic), greigite (Fe3S4) and pyrrhotite (Fe1-xS) by acidophilic Fe- and S-oxidizing bacteria and archaea. The hexavalent uranium is soluble in sulfuric acid solution (lixiviant) and is recovered in downstream hydrometallurgical processing to produce a concentrate (yellowcake). The acid bioleaching reactions are optimal at pH 1.5-3 as the low pH facilitates proton attack on minerals and alleviates the precipitation of metals in the leachate and on mineral surfaces. Uranium is extracted from ores on a commercial scale using heap, dump, and stope leaching processes. In some operations other metals can also be recovered as byproducts in the process.